Safety of Thioguanine in Pediatric Inflammatory Bowel Disease: A Multi-Center Case Series. Issue 6 (20th September 2022) - Bayoumy, Ahmed B.; Jagt, Jasmijn Z.; van Wering, Herbert M.; de Ridder, Lissy; Hummel, Thalia; Wolters, Victorien M.; Stapelbroek, Janneke; Benninga, Marc A.; Mulder, Chris J.J.; de Boer, Nanne K.H.; de Meij, Tim G.J.
Abstract : Objectives: Thioguanine (TG) has been shown as a safe alternative in adults with inflammatory bowel disease (IBD) who did not tolerate conventional thiopurines [azathioprine (AZA)/mercaptopurine]. However, data in pediatric IBD are scarce. Therefore, we aimed to assess the safety of TG as maintenance therapy. Methods: A retrospective, multicenter cohort study of children with IBD on TG was performed in the Netherlands. TG-related adverse events (AE) were assessed and listed according to the common terminology criteria for AE. Results: Thirty-six children with IBD (median age 14.5 years) on TG (median dose 15 mg/day) were included in 6 centers. Five AE occurred during follow-up [pancreatitis (grade 3), hepatotoxicity (grade 3) (n = 2), Clostridium difficile infection (grade 2), and abdominal pain (grade 2)]. All patients (n = 8) with a previously AZA-induced pancreatitis did not redevelop pancreatitis on TG. Conclusions: In pediatric IBD, TG seems a safe alternative in case of AZA-induced pancreatitis. Further research assessing long-term TG-related safety and efficacy is needed.